Profiling chromosomal‐level variations in gastric malignancies. Issue 11 (9th September 2022) - Negoto, Tetsuya; Jo, Minji; Nakayama, Izuma; Morioka, Motohiro; Takeuchi, Kengo; Kawachi, Hiroshi; Hirota, Toru
Abstract: Aneuploidy arises from persistent chromosome segregation errors, or chromosomal instability. Although it has long been known as a hallmark of cancer cells, reduced cellular fitness upon induced ploidy alterations hinders the understanding of how aneuploidy relates to cancer development in the body. In this study, we used FISH analysis targeting centromeres to indicate ploidy changes, and quantitatively evaluated the ploidy statuses of gastric tumors derived from a total of 214 patients, ranging from early to advanced disease. We found that cancer cells reveal a marked elevation of aneuploid population, increasingly in cases diagnosed in advanced stages. The expansion of the aneuploid population is well associated with p53 deficiency, consistent with its essential role in genome maintenance. Comparisons among multiple locations within the tumor, or between the primary and metastatic tumors, indicated that cancer cells mostly retain their ploidy alterations throughout primary tumors, but metastatic tumors may consist of cells with either increased or decreased levels of aneuploidy. We also found that a notable proportion of polyploid cells are often already present in chronic gastritis epithelia. These observations underscore that chromosome‐level variations are widespread in gastric cancers, shaping their genetic heterogeneity and malignant properties. Abstract : Through evaluating chromosome‐level variations in gastric cancer tissues, our observations demonstrate that ploidy alteration in gastric cancers shapes their heterogeneity and malignant properties.